SPS260 : Fundamental of sport biomechanics / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course discuses the anatomical and foundation of human motion. The discussion focuses on basic kinematic and kinetic concepts, human mobility system and structure and functioning of the human body in relation to physical forces that govern human motion